“METHODOLOGY FOR ORGANIZING AUDITS OF INSURANCE ORGANIZATIONS” (World Economics and Finance Bulletin, 2025)
The article discusses the specific features of insurance organizations and delves into issues related to organizing their accounting. Additionally, the process of conducting audits in insurance organizations is examined. The article also covers the procedures for managing the accounting of insurance organizations, conducting analyses, comprehensively evaluating the activities of insurance organizations, and the concept of conducting insurance audits on an international scale.
Keywords: Insurance organization; audit; internal control; financial reporting